Investigating Selected Denigrating Yorùbá Proverbs Inimical to Social Cohesion - Olofin, Olufunmilayo Lara; Odebiyi, Idowu Paul; Omisakin, Adeyemi Matthew (Advances in Social Sciences Research Journal, 2023)
National cohesion is a global trending issue in this century, consequent upon terrorist activities all over the world. This paper x-rays selected Yorùbá proverbs in relation to social cohesion. It examines the denigrating nature of the selected proverbs in a multilingual society. It also aims at determining existence of the proverbs till date and the extent of their usage for communication purposes. Ten purposively selected Yorùbá proverbs are scripted for completion by one hundred (100) undergraduate respondents between ages 15 and 35, to discover their level of awareness of and familiarity with the proverbs, using descriptive statistics analysis. The study draws insight from Communication Accommodation Theory, (CAT) (Giles, 1987 & Giles & Ogay, 2007). Results show that the proverbs are still in use and the youth are aware of these proverbs but in varying degrees.